2009
DOI: 10.1021/op900208y
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery and Development of a Safe, Practical Synthesis of ABT-869

Abstract: The discovery, development and implementation of two chemical routes to ABT-869 is reported. Optimization of the first-generation heterocycle formation and Suzuki coupling is briefly described. Key features of the second-generation synthesis include the development of a safe hydrazine condensation by utilizing an inorganic base to increase the onset temperature of exothermic decomposition. The second-generation Suzuki reaction is discussed in detail, culminating in the use of an oxygen monitor as a PAT to maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…We evaluated the binding affinities of 28 to the family of BET proteins and its selectivity over bromodomain-containing proteins in the BROMOscan assays by DiscoverX, 26 and the results are summarized in Table 6. The data showed that 28 binds to both the BD1 and BD2 domains of BRD2, BRD3, BRD4, and BRDT BET proteins with high affinities (K d = 0.49−2.2 nM).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We evaluated the binding affinities of 28 to the family of BET proteins and its selectivity over bromodomain-containing proteins in the BROMOscan assays by DiscoverX, 26 and the results are summarized in Table 6. The data showed that 28 binds to both the BD1 and BD2 domains of BRD2, BRD3, BRD4, and BRDT BET proteins with high affinities (K d = 0.49−2.2 nM).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Most boronic acids or pinacolboronic esters are commercially available. Others were synthesized according to known methods reported previously. Suzuki coupling ,, of the corresponding boronic acids or pinacolboronic esters and 7 or S10 followed by reverse phase HPLC purification furnished pure final products as salts of trifluoroacetic acid.…”
Section: Chemistrymentioning
confidence: 99%
“…Others were synthesized according to known methods reported previously. 37−39 Suzuki coupling 37,40,41 of the corresponding boronic acids or pinacolboronic esters and 7 or S10…”
Section: ■ Chemistrymentioning
confidence: 99%
“…Recently, many pharmacologically important compounds with substituents at the 4-position of indazole have been developed for pre-clinical testing, such as ABT-869 17 and ABT-102. 18,19 Reliable and efficient syntheses of these indazoles were required to provide access to large quantities of bulk drug for further studies.…”
mentioning
confidence: 99%